2013
DOI: 10.1074/jbc.m112.441469
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B Regulates Pyruvate Kinase M2 Tyrosine Phosphorylation

Abstract: Background: Tyrosine phosphorylation of PKM2 inhibits its activity; however, the phosphatase(s) that regulates PKM2 phosphorylation remains unidentified. Results: PKM2 is a novel PTP1B substrate and PKM2 Tyr-105 and Tyr-148 are key sites that mediate the interaction. Conclusion: PTP1B regulates PKM2 tyrosine phosphorylation and activity in adipocytes. Significance: These findings provide new insights into the regulation of adipose PKM2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 64 publications
3
45
0
Order By: Relevance
“…In addition, fibroblast growth factor receptor 1 phosphorylates PKM2 on Tyr-105, which inhibits the formation of active, tetrameric PKM2 by disrupting binding of PKM2 cofactor fructose-1,6-biophosphate (17). Protein-tyrosine phosphatase 1B reverses this phosphorylation (18). A-Raf can bind to and phosphorylate PKM2 on serine residues, inducing a transition of dimeric to tetrameric active form of PKM2 (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, fibroblast growth factor receptor 1 phosphorylates PKM2 on Tyr-105, which inhibits the formation of active, tetrameric PKM2 by disrupting binding of PKM2 cofactor fructose-1,6-biophosphate (17). Protein-tyrosine phosphatase 1B reverses this phosphorylation (18). A-Raf can bind to and phosphorylate PKM2 on serine residues, inducing a transition of dimeric to tetrameric active form of PKM2 (19).…”
mentioning
confidence: 99%
“…Compared with normal tissues, most tumors exhibit a significant increase of glucose utilization, namely the Warburg effect (1). Such a characteristic of increased glucose uptake, which accompanies the aerobic glycolysis, has been exploited for diagnosis of cancer using 18 F-deoxyglucose position emission tomography (2). Due to the changes of glycolytic enzymes, tumor cells shift glucose metabolism from oxidative phosphorylation to glycolysis even in the presence of oxygen.…”
mentioning
confidence: 99%
“…Consistent with finding in vitro, quantitative RT-PCR analysis indicated that the expression of CPT1 was significantly increased when HDIO zebrafish was fed 10 µg/mL of FCSN ( Figure 4B). Moreover, we found that 10 µg/mL of FCSN supplemented HDIO zebrafish significantly induced the increased expression of pyruvate kinase M2 (PK-M2), which decrease in adipose tissue in obese animal model [31], compared to HDIO zebrafish. Here, we provided a part of evidence that FCSN may lead to suppress body fat accumulation through stimulating both energy metabolism and β-oxidation in HDIO zebrafish.…”
Section: Effects Of Fcsn On Energy Metabolism and β-Oxidation In Highmentioning
confidence: 93%
“…PTP1B-deficient brown adipose tissue [122] and brown adipocytes [81] exhibit increased AMPK activity. In addition, recent studies identify pyruvate kinase M2 (PKM2) as a PTP1B substrate [64]. Pyruvate kinase (PK) is a rate-limiting glycolytic enzyme that catalyzes the generation of pyruvate and ATP from phosphoenolpyruvate (PEP) and ADP [123] (Figure 1).…”
Section: Ptp1b Substrates and Metabolic Regulationmentioning
confidence: 99%